Opinion mining and sentiment analysis - Pang, Bo; Lee, Lillian (Now, 2008)
An important part of our information-gathering behavior has always been to find out what other people think. With the growing availability and popularity of opinion-rich resources such as online review sites and personal blogs, new opportunities and challenges arise as people now can, and do, actively use information technologies to seek out and understand the opinions of others. The sudden eruption of activity in the area of opinion mining and sentiment analysis, which deals with the computational treatment of opinion, sentiment, and subjectivity in text, has thus occurred at least in part as a direct response to the surge of interest in new systems that deal directly with opinions as a first-class object.
Keywords: dolování dat; internetové sociální sítě; zpracování dat; počítačové zpracování textu; data mining; Internet social networks; data processing; computer text processing; studie; studies